Tattoo and piercing as elements of corporal building - Alberto González García (Universidad de Alicante, 2014)
Tattooing and body piercing are a reflection of the human need to decorate their body. Young people create significant senses that create other identities. The target of this research is to reveal the meaning of the tattooed skin to understand this social phenomenon. We understand these practices as a network of meanings, expressed in attitudes and feelings, which is crossed by the gender, the experience of pleasure VS pain and resistance to the dominant aesthetic. We have selected a sample of six men and six women of all clients served in 2009 on a tattoo and piercing Clinic to conduct in-depth interviews. There is a difference between feminine and masculine, both in design and corporal areas such as the decision leading to tattooing or piercing, and attributed meaning. Women choose these body practices with an aim of playing and seduction, they feel under the gaze of society, like men, but men do not feel as strongly beauty standards than women. Customers feel discrimination in the family and work, and they explain that tattoos and piercings are not valued as an artistic element in society.